Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.3390/s6080796
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Optic Biosensor Employing Alexa-Fluor Conjugated Antibody for Detection of Escherichia coli O157:H7 from Ground Beef in Four Hours

Abstract: Abstract:Fiber optic biosensor has a great potential to meet the need for rapid, sensitive, and real-time microbial detection systems. We developed an antibody-based fiber-optic biosensor to rapidly detect low levels of Escherichia coli O157:H7 cells in ground beef. The principle of the sensor is a sandwich immunoassay using an antibody which is specific for E. coli O157:H7. A polyclonal antibody was first immobilized on polystyrene fiber waveguides through a biotin-streptavidin reaction that served as a captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…This generates an optical signal, the strength of which is proportional to specific analyte binding. To convert these assays from a laboratory-based 96-well plate format to a smaller, more portable biosensor system, optical fibers have been employed for the detection of whole bacterial cells (35,36). Fiber optic biosensors (FOB) typically comprise a source of light which passes through optical fibers containing immobilized bioreceptors to a photon detector.…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…This generates an optical signal, the strength of which is proportional to specific analyte binding. To convert these assays from a laboratory-based 96-well plate format to a smaller, more portable biosensor system, optical fibers have been employed for the detection of whole bacterial cells (35,36). Fiber optic biosensors (FOB) typically comprise a source of light which passes through optical fibers containing immobilized bioreceptors to a photon detector.…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…The system holds potential to meet the need for simple, rapid, sensitive, and antigenspecific real-time detection for its structural design and assay principle. Several investigations have already been demonstrated using the same principle of the fluorescent immunoassay system, such as Escherichia coli O157:H7 (Geng et al 2006;DeMarco and Lim 2001), Salmonella (Valadez et al 2009), and Listeria monocytogenes (Geng et al 2004). However, to our knowledge, there has been no report about detection of environmental allergens using the fluorescence immunoassay system.…”
Section: Introductionmentioning
confidence: 92%
“…A fluorescence-based fiber-optic biosensor for detecting E. coli O157:H7 in ground beef samples was developed by Geng et al [78]. The authors reported sensitivity of 10 3 CFU/ml in pure cultures and of 1 CFU/ml in artificially contaminated ground beef samples after 4 h enrichment using a sandwich immunoassay.…”
Section: Fluorescence-based Biosensorsmentioning
confidence: 99%